Pemulihan Psikososial Anak Pasca Gempa: Strategi Trauma Healing Berbasis Komunitas - Sutikno, Ari Yudha Caesar; Rahmat, Hayatul Khairul (Journal of Current Research in Humanities, Social Sciences, and Business, 2025)
Earthquakes, as sudden natural disasters, can cause serious psychological trauma, especially in children. This article aims to describe the implementation of community-based trauma healing to support the emotional recovery of children affected by earthquakes. Based on direct experiences in volunteer work and field observation at post-earthquake shelters, community-based approaches using social activities, art, and play were found to be effective in reducing trauma symptoms. Trauma healing serves not only to address short-term emotional distress, but also to help restore children’s sense of safety and hope in post-disaster environments.